Analisa Variasi Bahan Bakar Terhadap Performa Motor Bensin 4 Langkah - Wibowo, Nizar Bayu; , Ir. Sartono Putro, MT; , Ir. Subroto, MT (2016)
This study aimed to analyze the effect of the use of premium fuel, pertalite, and pertamax to the performance of the motor. This test uses a motorcycle Yamaha Jupiter Z 110 cc. Testing the performance of a motorcycle was done by using dynotest (sportdyno V3.3). testing performed ternately for each fuel engine with a variation of the engine rotation 4000-10000 rpm to 250 rpm rise at 3 gear transmission in order to obtain a comparison of torque (T), power (P), and specific fuel consumption (KBBS). The results showed that the torque, power, and best KBBS generated by premium fuel operation with the air condition setting screw is rotated 05 left of the state of idling. The torque generated by 8,07 Nm at 6031 rpm rotation. The power generated by 8 HP at 7772 rpm rotation. KBBS generated at 0.134 kg / kw.h at 5500 rpm rotation.